EFEITO DE EXTRATOS DE ARISTOLOCHIA LAGESIANA (ARISTOLOCHIACEAE) SOBRE A LAGARTA-DA-SOJA, ANTICARSIA GEMMATALIS (LEPIDOPTERA: NOCTUIDAE) - Vieira, L.; Pascoli, I. De [UNESP]; Bortoli, S.a. De [UNESP]; Lopes, L.m.x. [UNESP] (Instituto Biológico, 2021)
Various reports have shown that species of the genusAristolochia, whose plants are distributed throughout Brazilian territory, can produce biological effects. The objective of the present study was to evaluate the action of extracts of Aristolochia lagesianaUle. var. intermedia Hoehne (Aristolochiaceae) on the velvetbean caterpillar. The bioassays were conducted at the Biology and Rearing Insect Laboratory of the FCAV/UNESP in Jaboticabal, state of São Paulo, SP, Brazil, and at the Chemistry Organic Laboratory of the IQ/UNESP in Araraquara, SP. The relative toxicity of the extracts was evaluated through the topical application of 1 µL of extract solution on the mesothorax of third-instar Anticarsia gemmatalis larvae, using a microsyringe, connected to a microapplicator apparatus. Plants were extracted in acetone, which was completely evaporated before the application. For applying on insects, extracts were diluted in ethanol to obtain the following dosages: 6.0, 9.6, 13.2, 16.8, 20.4 and 22.0 mg/?L. Extracts of A. lagesiana increased the duration of the larval phase, decreased the pupae weight and also the larval viability.

Vários relatos de atividades biológicas podem ser encontrados nas espécies de plantas pertencentes ao gênero Aristolochia (Aristolochiaceae), cujas plantas estão distribuídas em todo o território nacional. Visando a obtenção de mais informações sobre essas plantas, avaliou-se a ação de extratos de Aristolochia lagesiana Ule. var. intermedia Hoehne sobre Anticarsia gemmatalis Hüebner, 1818 (Lepidoptera: Noctuidae). O experimento foi conduzido no Laboratório de Biologia e Criação de insetos da FCAV/ UNESP – Jaboticabal e no Laboratório de Química Orgânica do IQ/ UNESP – Araraquara. A toxidade relativa dos extratos foi determinada através da aplicação tópica de uma gota de 1 µL de solução, de cada extrato, que foi aplicada no mesotórax de lagartas de terceiro instar, utilizando-se um aparelho microaplicador. As plantas foram extraídas em acetona, que foi evaporada antes da aplicação e, para isto, os extratos foram re-solubilizados em etanol para obtenção das seguintes dosagens: 6,0; 9,6; 13,2; 16,8; 20,4 e 22,0 mg/?L. Os extratos de A. lagesiana alongam a duração do período larval, reduzem o peso de pupas e também diminuem a viabilidade larval de A. gemmatalis .
EFFECT OF EXTRACTS OF ARISTOLOCHIA LAGESIANA (ARISTOLOCHIACEAE) ON VELVETBEAN CATERPILLARS
Keywords: Insecticide plant; deleterious effects; acetone extracts; Planta inseticida; efeitos deletérios; extratos acetônicos